Changes in Racial Apathy Among White Young Adults: A Five‐Year National Panel Study. Issue 1 (24th June 2022) - Brown, Tony N.; Culver, Julian; Bento, Asia; Gorman, Quintin
Abstract : This study investigates changes in racial apathy among white young adults using nationally representative panel survey data from the NSYR. Our regression models include social background, social values, and academic orientation variables specified as important correlates of racial apathy in prior cross‐sectional studies. We also include interracial contact variables, which existing studies neglect. According to intergroup contact theory, interracial contact should predict decreases in racial apathy. We find variables specified as important correlates in prior cross‐sectional studies do not explain changes in racial apathy across time. Surprisingly, interracial friendship associates negatively with increases and decreases in racial apathy. Further, interracial dating predicts increases in racial apathy across time. These findings suggest racial apathy may be dissimilar to other forms of white racial prejudice and interracial contact may be an ineffective method to reduce contemporary forms of white racial prejudice.